On becoming library and information professional exploring competencies and the curriculum - Galarosa, Charmaine Jeremy S.; Santos, Yhna Therese, P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
Since library and information science graduates are expected to be equipped with more competencies due to their changing roles and nature of work, an analysis of competencies that can be acquired from an LIS education and the needed competencies by the LIS graduates have to be conducted to know the necessary revisions to be made for curriculum improvement, specifically, for the LIS courses and electives, of the B LIS program of UP SLIS. Thus, this study focused on the gap between the competencies that can be acquired from the LIS courses and electives offered in the current B LIS curriculum of the UP SLIS and competencies of its B LIS Graduates working in different occupational contexts.
A total of 17 selected B LIS graduates of UP SLIS working in different occupational context around Metro Manila were interviewed for their competency needs. The most recent, printed curriculum and all the LIS course and electives' syllabi available were used for content analysis of the competencies that can be acquired from them. A comparative analysis was done thereafter in order to know the gap the exists between the two.
The data gathered from the interviews and content analysis of the syllabi revealed that: (a) LIS graduates are expected to do more roles aside from the traditional librarianships and therefore, should be competent enough, not only with the technical librarianship skills, but also in other fields related to LIS; (b) personal competencies, archives and records management, and IT-related competencies are deemed to the most valued competencies of the LIS graduates and are the most required in carrying out their daily tasks; (c) the LIS courses and electives in the current B LIS curriculum of UP SLIS impart enough technical competencies to their graduates; and (d) a slight mismatch between the needed competencies of LIS graduates and the competencies that can be acquired from LIS courses and electives that are currently offered in the B LIS curriculum.
This study recommends the following: (a) there should have a deeper approach and/or require courses on ICT, archives and records management courses, digital and preservation, psychology, education, and ethics course; (b) a similar study with a quantitative approach (i.e., survey) should be done for a wider sample of LIS graduates so as to obtain a more accurate data for further analysis of their needed competencies; (c)a focus group discussion (FGD) for a similar study with a quantitative approach should be made for an in-depth analysis of the needed competencies of the LIS graduates; and, (d) a further study of the B LIS curriculum as a whole should be conducted for a broader view of what could the program actually impart to its students.
Thesis (Bachelor of Library and Information Science)